ACCURACY OF TWO-DIMENSIONAL SHEAR WAVE ELASTOGRAPHY FOR DIAGNOSING LIVER FIBROSIS IN PATIENTS WITH CHRONIC HEPATITIS C - SAMAAT, M; AMIR, SI; NOOR , A; QURESHI, J; HASSAN, WU; SHABBIR, UB (Biological and Clinical Sciences Research Journal, 2023)
The prospective study was conducted in tertiary care hospitals from January 2021 to January 2022 to assess the diagnostic accuracy of two-dimensional shear wave elastography for evaluating liver fibrosis in patients with HCV by using liver biopsy and METAVIR staging as a diagnostic reference. Two hundred fifteen patients who fulfilled the study criteria were included. 2D SWE examination was done by two experienced radiologists, blinded to the clinical and histological data of the participants, independently. The METAVIR scoring system was used for staging liver fibrosis. Biochemical tests for serum liver fibrosis biomarkers were also performed. In addition to patients, 25 healthy controls were included. Results showed that SWE was successfully performed in 97.6% (210/215) cases. In the study group, the median SWV was 1.75 (0.95-2.86) m/s. In the control group, the median SWV was 1.29 (1.04-1.48) m/s. 30 patients had stage F0, 42 had F1, 30 had F2, 40 had F3 and 68 had F4. For necro inflammation, 9 patients had A0, 126 had A1, 71 had A2, and 4 had A3. For stenosis, 169 patients had S0, 35 had S1, 3 had S2 and 4 had S3. The higher fibrosis stages were positively correlated with increased SWV (P<.0001). There was a significant negative correlation between SWV and Alb and Plt and a significant positive correlation between SWV and M2BPGi, IV-c-7S, HA, PT, ALT, AST, and T.Bil. AUCs for 2D SWE were higher than serum biomarkers (P<0.05). In conclusion, 2D SWE has higher diagnostic accuracy than serum liver fibrosis biomarkers and is significantly associated with the severity of fibrosis.